Blood Pressure Status among Registered Commercial Vehicle Drivers in University Of Benin, Edo State, Nigeria - Fidelis , Uchendi Okafor; Agharese, Efe-Aigbovo (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
This study was designed to assess the blood pressure status of the campus commercial vehicle drivers in the University of Benin, Edo State of Nigeria, aimed at establishing blood pressure database for instituting intervention programmes for cardiovascular disease prevention. The population of the study was 250 males and a sample size of 154. A descriptive, non experimental design was employed and this research was carried out between Septembers and November, 2014. A total of 154 campus drivers completed an interviewer administered questionnaire/checklist form. A purposive sampling technique was employed. The reliability of 0.74 was established using the test re-test method. Data were analyzed using frequency counts and percentage as well as chi-square to test the hypotheses.. Results revealed that 61% of the respondents had normal blood pressure with ranges of 100/70 to 120/80mmHg systolic and diastolic while 39% of the respondents had abnormal blood pressure ranges of 130/90 to 140/100mmHg. Risk factors such as age and body mass index (BMI) have been found to be significant in the increased blood pressure among drivers. The study also showed that (100%) of the respondents were aware of hypertension. Despite the awareness, 41.6% of the respondents had rarely had a blood pressure check.